Dark Triad of Personality and Lying Behavior of Adolescents: Mediating Role of Social Skills - Mubeen Anwar, Aisha Zubair (Pakistan Journal of Psychology, 2019)
The present study attempted to explore the predictive role of dark triad of personality in social skills and lying behavior of adolescents. It was also intended to determine the mediating role of social skills in predicting lying behavior. Study Sample (N = 450) comprising of students with age range from 13 to 17 years was drawn from the government and private schools. Dark Triad of Personality Scale (Paulhus, 2013), Matson Evaluation of Social Skills (Matson, Rotatori, & Helsel, 1983), and Lying Scale (Finkenauer, Engels, & Kooten, 2006), were employed to appraise the major constructs of the study. Results showed that dark triad traits negatively predicted social skills and positively predicted lying behavior; whereas lying behavior was positively related with social skills. In addition, social skills mediated the relationship between dark triads of personality and lying behavior of adolescents. Gender differences indicated that boys reflected higher dark triad traits and lying behavior as compared to girls; while non-significant gender differences were found in relation to social skills.